Self-similar reconfigurable low-pass MEMS filters using coplanar waveguide based on silicon. (December 2021) - Guo, Xinglong; Wang, Jiushan; Cui, Zihao
Highlights: A low-pass filter has been designed using periodic self-similar coplanar waveguide. The filter is used in large integrated or hybrid circuits without require wire bonding. The paper gives the MEMS surface fabrication processing of the filter. The MEMS switch has relatively lower driven voltag with 26 V. Abstract: This paper presents a low-pass filter based on microelectromechanical system using periodic self-similar coplanar waveguide. The device is fabricated on 525-μm high-resistivity silicon substrate using surface micromachining process which partial compatible process with IC. The tunable resonant frequency is achieved using micro-electromechanical contact capacitive switches. The total area of the filter is about 6 mm 2 including bias lines and pads. The parameters of the filter has been analyzed by applying the Ansoft-HFSS. When switch is on original state, the measured results of the filter show that the 3-dB cutoff frequency is 16.15 GHz with the average insertion loss of 0.95 dB. The 3 dB cut-off frequency of the reconfigurable filters is 22.85 GHz with the average insertion loss of 2.33 dB. A relatively lower driven voltage is around 26 V.